2009
DOI: 10.1007/s00775-009-0502-z
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive synthesis and biodistribution study of β-elemene–99mTc(CO)3 conjugates

Abstract: Beta-elemene, (5S,7R,10S)-(-)-(1-methyl-1-vinyl-2,4-diisopropenylcyclohexane), is an anticancer agent from traditional Chinese herbal medicine. Three novel (99m)Tc(CO)(3)-beta-elemene conjugates were synthesized successfully, and compared with beta-elemene exhibited improved water solubility. A biodistribution and micro single photon emission computed tomography image study showed there is a visible accumulation in Lewis lung cancer tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Sun et al 99 synthesized the β-elemene-99m Tc(CO) 3 (H 2 O) 3 + conjugate 9. The oil-water partition coefficient was reported as P=199.5±4.…”
Section: Radioactive Conjugatementioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al 99 synthesized the β-elemene-99m Tc(CO) 3 (H 2 O) 3 + conjugate 9. The oil-water partition coefficient was reported as P=199.5±4.…”
Section: Radioactive Conjugatementioning
confidence: 99%
“…Micro-single-photon emission computed tomography (SPECT) images indicated that it had a significant accumulation in tumor regions after iv injection. 99…”
Section: Radioactive Conjugatementioning
confidence: 99%